2017
DOI: 10.17509/jpjo.v2i2.8183
|View full text |Cite
|
Sign up to set email alerts
|

Motivasi Masyarakat Melakukan Olahraga Rekreasi Melalui Program Car Free Day Di Jakarta

Abstract: AbstrakKegiatan masyarakat dalam hal melakukan olahraga rekreasi saat ini masih sangatlah kurang. Selain faktor kesadaran akan pentingnya olahraga yang berasal dari dalam diri sendiri, faktor lain yang menghambat masyarakat untuk melakukan olahraga rekreasi adalah mengenai sarana dan prasarana yang tersedia untuk mendukung kegiatan tersebut. Tujuan dari penelitian ini adalah untuk mengetahui motivasi masyarakat melakukan olahraga rekreasi melalui program Car Free Day (CFD) di Jakarta pada tahun 2017. Pendekata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
0
4
0
12
Order By: Relevance
“…At the other hand, there are little clues that can be obtained from past studies to explain the motivation to visit CFD among Indonesian people. One similar study found that the motivation of Indonesian people to visit CFD in Jakarta is to do recreational sports that can be defined as any pleasurable physical activities that produce positive benefits [5]. Another study found factors that positively affect the intention of Indonesian people to visit CFD are including utility of CFD (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…At the other hand, there are little clues that can be obtained from past studies to explain the motivation to visit CFD among Indonesian people. One similar study found that the motivation of Indonesian people to visit CFD in Jakarta is to do recreational sports that can be defined as any pleasurable physical activities that produce positive benefits [5]. Another study found factors that positively affect the intention of Indonesian people to visit CFD are including utility of CFD (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This means that with this concept the development of community sports can continue in accordance with its objectives in maintaining health, improving fitness, and carrying out social relations between communities (Dowling et al, 2021). In line with one of the goals of community sports developed in Indonesia, namely social relations (Kasriman, 2017), found research on community sport in the UK that participation enables young people to increase the component of positive psychological capital, and offers a further theoretical point of view to understand and deepen the relationship between participation in sport and social inclusion (Morgan et al, 2019). In the development of community sports, there are two factors, namely the contribution of education and work which are indeed a common goal in improving social relations through community sports participation in the community.…”
Section: Community Sports Policy In Pattern Developmentmentioning
confidence: 94%
“…3 Tahun 2005 Tentang Sistem Keolahragaan Nasional yaitu, Olahraga rekreasi adalah olahraga yang dilakukan oleh masyarakat dengan kegemaran dan kemampuan yang tumbuh dan berkembang sesuai dengan kondisi dan nilai budaya masyarakat setempat untuk kesehatan, kebugaran dan kegembiraan (Kasriman, 2017).…”
Section: P R O S I D I N G S E M I N a R N A S I O N A L #J I L I D 1...unclassified